Peace Shang / Hanif Hamim ... [et al.] - Hamim, Hanif; Jamil, Nurul Naqiah; Adam, Nor Siti Rafidah Ayu; Hisham, Nur Syazwani Ahmad; Mohd Ariffin, Mohamad Aniq Syahmi; Mohd Yusof, Mohammad Yusfairul Aizzat (2016)
Peace Shang is located in Lot 12, Jalan Klebang Besar, 75200 Melaka that allows the entire family to have their cravings satisfied in one convenient location. Peace Shang that serves healthy banana yogurt sticks with variety of toppings, accepts appointments as well as walk ins. Peace Shang is able to serve the entire family in one quick, convenient visit. While we have competitors against us which is Coconut Shake Pantai Klebang will excel due to its attention to detail regarding customer service. Through unheralded customer attention, Peace Shang will slowly but surely gain market share as it services the entire family, creating long-term relationships. People across Malaysia have decided to try our new product when they want to fulfill their cravings, for example to have their dessert through different ways of presentation. Peace Shang has foreseen this opportunity to provide the healthiest quality of banana yogurt sticks and presentation to all people. We, Peace Shang saw the oppprtunity that this business has the potential of success provided that it is handled efficiently. .The people have always needed to try healthy desserts being made into unique ways which they, have never thought of doing. Peace Shang sees this as a way to prosper in Chismarket, by taking advantage of all these people's need.